Exponential growth, high prevalence of SARS-CoV-2 and vaccine effectiveness associated with Delta variant - Elliott,P; Haw,D; Wang,H; Eales,O; Walters,C; Ainslie,K; Atchison,C; Fronterre,C; Diggle,P; Page,A; Trotter,A; Prosolek,S; et al. (Science, 2021)
SARS-CoV-2 infections were rising during early summer 2021 in many countries associated with the Delta variant. We assessed RT-PCR swab-positivity in the REal-time Assessment of Community Transmission-1 (REACT-1) study in England. We observed sustained exponential growth with average doubling time (June-July 2021) of 25 days driven by complete replacement of Alpha variant by Delta, and by high prevalence at younger less-vaccinated ages. Unvaccinated people were three times more likely than double-vaccinated people to test positive. However, after adjusting for age and other variables, vaccine effectiveness for double-vaccinated people was estimated at between ~50% and ~60% during this period in England. Increased social mixing in the presence of Delta had the potential to generate sustained growth in infections, even at high levels of vaccination.